Komparasi Pemikiran Syaikh Nawawi Al-Bantani dalam Kitab Qut Al-Habib Al-Gharib dengan Hukum Positif Mengenai Praktik Poligami - Fahmi Aunillah; Dzulkifli Hadi Imawan (Mutawasith: Jurnal Hukum Islam, 2025)
The issue of polygamy often becomes a complicated problem in family life. It is not merely for the public, even Muslim scholars and intellectuals often face challenges in discussing this topic. In practice, polygamy is a very complex and difficult thing to do. This is a descriptive analytical research, purposely to provide an in-depth description and explanation of the subject and object of research through a library research approach. The results of this study showed that the comparison of the concept of polygamy in the perspective of positive law, Islamic law, and the Book of Qut al-Habib al-Gharib has shown a number of important differences. In positive law, a husband who wants to practice polygamy is required to obtain the consent of his wife or existing wives. This consent must be given either verbally or in writing. On the other hand, in Islamic law, there is no requirement for the wife's consent to practice polygamy. In the book Qut al-Habib al-Gharib by Sheikh Nawawi al-Bantani, it is stated that a man is not allowed to marry a female slave unless he has fulfilled certain conditions set by the sharia.